Peningkatan Kesadaran Pencegahan Pernikahan Dini pada Remaja melalui Pembentukan Program Pusat Informasi Konseling Temaja (PIK-R) di SMA Nahwa Cantigi - Antri Ariani; Ecih Winengsih; Linda Rofiasari; Risma Mulyani (LPPM Akbid Harapan Ibu Pekalongan, 2025)
Marriage at a young age can have a negative impact on health, both physically and psychologically. Perception is one of the factors that influence adolescents' decisions towards early marriage. Adolescents' perception of early marriage is greatly influenced by three main aspects, namely cognitive, affective, and conative. In Indonesia, early marriage has reached alarming levels. Based on UNICEF data as of the end of 2022, Indonesia is currently ranked 4th in the world and 2nd in ASEAN, with a total of nearly 1.5 million cases. The method used in this activity is the provision of education through counseling with video communication media, leaflets and the provision of materials. Participants totaled 65 students of Nahwa Cantigi High School. Participants were given a questionnaire after providing educational materials, the results were obtained that more than half of the adolescents had good cognitive aspects (73.8%), and more than half of the adolescents (54%) did not support early marriage. And in the conative aspect, adolescents have a good or disagree perception of early marriage as much as (63%). Based on cognitive, affective and conative aspects, more than half of adolescents are well informed, do not support early marriage and are not ready to face these conditions. From the results of this community service, it is hoped that health workers in the region can consistently provide information and counseling to students related to early marriage. And the establishment of a youth counseling information center (PIK-R) program can continue in the future.